Prognostic Significance of PNI in Patients With Pancreatic Head Cancer Undergoing Laparoscopic Pancreaticoduodenectomy - Jiang, Peng; Li, Xiaocheng; Wang, Shupeng; Liu, Yahui (Frontiers in Surgery, 2022)
Background Recently, several prognosis indicators based on inflammatory and nutritional factors, such as the neutrophil-to-lymphocyte ratio (NLR), plated-to-lymphocyte (PLR), lymphocyte-to-monocyte (LMR) and prognosis nutritional index (PNI), have been proposed as prognosis factors for several cancers. However, few studies have looked into PNI. The goal of this research was to see if preoperative PNI had any predictive value in patients with pancreatic head cancer who were having a laparoscopic pancreaticoduodenectomy. Methods From February 11, 2018 to May 31, 2019, two hundred and fifty-one pancreatic head carcinoma patients were retrospectively enrolled. The receiver operator characteristic (ROC) curve was used to determine the cut-off value. Patients were divided into two groups: PNI > 45.1 (high PNI group) and PNI < 45.1 (low PNI group), and clinic-pathological data was compared between the two groups. The link between PNI and NLR, PLR, and LMR, and their effect on overall survival. In addition, the factors of postoperative survival were analyzed univariate and multivariate. Results PNI, NLR, PLR and LMR cut-off values were 45.1, 3.7,287.2 and 3.6, respectively. Between the two groups of patients, the low PNI group exhibited considerably higher PLR and lower LMR. PNI had a negative correlation with PLR and NLR (r = −0.329, p < 0.001 and r = 0.170, p = 0.014), but a positive correlation with LMR (r = 0.476, p < 0.001). The high PNI group had a considerably greater survival rate than the low PNI group (median survival days, 217 vs. 468, log-rank = 45.92, p < 0.001). PNI < 45.1(HR: 0.357, 95 percent CI, 0.263–0.485, p < 0.001) and LMR <3.6(HR: 0.705, 95 percent CI, 0.528–0.942, p < 0.018) were revealed to be possible predictive variable in univariate analysis. Only PNI <45.1 was found to be an independent predictive factor in multivariate analysis (HR: 0.359, 95%CI,: 0.256–0.502, p < 0.001). Conclusions Our findings shoe that PNI is linked to a variety of systemic inflammatory response and can be used to predict survival in individuals with pancreatic head cancer.